Interstellar Cinderella - Underwood, Deborah; Hunt, Meg (San Francisco : Chronicle Books, 2015)
In this outer space adaptation of the fairy tale in rhyme, Cinderella dreams of becoming a spaceship mechanic.
Keywords: Cinderella (Legendary character) -- Juvenile fiction; Cinderella (Tale) -- Adaptations; Stories in rhyme; Stories in rhyme; Mechanics -- Fiction; Sex role -- Fiction; Outer space -- Juvenile fiction; Outer space -- Fiction; Fairy tales